SURG-09. Benefits of laser interstitial thermal therapy in the treatment of biopsy-proven radiation necrosis. (9th August 2021) - Lerner, Emily; Srinivasan, Ethan; Sankey, Eric; Grabowski, Matthew; Griffin, Andrew; Howell, Elizabeth; Otvos, Balint; Tsvankin, Vadim; Akit, Ahmet; Joshi, Krishna; Barnett, Gene; Fecci, Peter; et al.
Abstract: Introduction: Laser interstitial thermal therapy (LITT) is a minimally-invasive treatment option often used for patients with deep-seated intracranial lesions. It has been implemented as a definitive treatment for radiation necrosis (RN), which occurs in 9–14% of patients after stereotactic radiosurgery (SRS) for brain metastases (BM). Medical management (MM) with steroids is a common first-line therapy, with variable response and numerous side effects, especially regarding immunotherapy. Methods: Patients with biopsy-proven RN after SRS for BM who received LITT or MM at two academic centers were retrospectively reviewed. Treatment failure was defined as radiographic progression that necessitated a change in management. Measurements of total (TLV) and contrast-enhancing lesion volume (ceLV) were obtained from MRI by semi-automated analysis using the BrainLab iPlan Cranial 3.0 software. Results: Seventy-two patients were followed for 10.0 (4.2–25.1) months and 57 (79%) received LITT. Steroid cessation occurred at a median of 37 days post-LITT compared to 245 days after MM (p<0.01). On Kaplan-Meier analyses, there was no significant difference between the two groups in overall survival (LITT median of 15.2 months vs 11.6 months, p = 0.60) or freedom from local progression (13.6 months vs. 7.06 months), though LITT trended to show a benefit in both metrics. When controlled for follow-up duration, patients treated with LITT were three times more likely to be weaned off steroids prior to the study endpoint compared to those who were medically managed (p=0.003). The LITT cohort demonstrated a general radiographic trend of initially increased CeLV followed by contraction, with significant decreases from pre-operative at 10–12 months (p<0.01). The MM group did not demonstrate any statistically significant radiographic trends. Conclusion: These results suggest that LITT for RN significantly reduces the time to steroid cessation and characterize a stereotyped radiographic response to LITT. Future prospective studies will be important to their validation.